STRATEGI IRAN DALAM MENGHADAPI EMBARGO PERDAGANGAN AMERIKA SERIKAT DAN EROPA (IRAN STRATEGY ON FACING USA AND EUROPE TRADE EMBARGO - Muhammad Arief Zuliyan (HI 15 UMY 441, 2015)
*441 This article explains the Iran strategies in order to articulate his national interest under United States of America and Europe embargo from 2006 to 2015. Even, The embargo has big negative effect to Iran’s economy and politic but because of good Iran foreign policy by boardening relations to whom has big potencial, Iran can survive and strenghten economic and politic international. Iran coorporates with China and Russia who has very good bergainning position in the term of International Politics, Economics and Millitary. Iran boardens the relations to Asia and Latin America in order to get new community with the same famework. And also, Iran goes to International Organizations such as; Shanghai Cooperation Oganizaton (SCO) and Brazil, Russia, India, China and South Africa (BRICS), the developing countries organization which has big potencial economics in the world. Key words: Iran. Embargo. International Coorporations